Developing a Procedure of Extracting Total Polysaccharide from Dendrobium Nobile Lindl. in Vietnam - Nguyen, Thi Viet Thanh (JST: Engineering And Technology For Sustainable Development, 2021)
Dendrobium nobile Lind., also known as Hoang thao dui ga, is a species of plant belonging to the genus Dendrobium, a large genus of the Orchidaceae. This is a medical plant used in many remedies in China and Vietnam. Polysaccharide from this species has been shown many valuable biological activities such as hypoglycemia antioxidant and anti-cancer. In this paper, a procedure for extracting total polysaccharide by aqueous solvent from D.nobile based on the survey of factors: temperature, time, material/solvent ratio affecting this extraction process was proposed. The total polysaccharide content was also determined according to phenol-sulfuric acid method.